THE IMPACT OF GASOLINE-TO-LPG FUEL CONVERSION ON ENGINE PERFORMANCE IN ELECTRONIC FUEL INJECTION MOTORCYCLES: AN EXPERIMENTAL ANALYSIS - Sentosa, Ilham; Mukarrama, St. Khaeratul (Jurnal Pendidikan Vokasi Otomotif, 2025)
This study aims to determine the performance analysis in converting gasoline fuel to LPG fuel on motor performance on electric fuel injection-based motorcycles and engine performance with the use of LPG gas fuel and gasoline. with a 110 cc engine at engine speeds of 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 and 5000 rpm. Instrument testing was carried out at Ernest Racing Home (Makassar). This research method is "Pre-Experimental Designs" (pre-Experiment). Testing uses a dyno test where the test data produces print out data, analyzed using a descriptive investigation method. The results of the experiment on a 110 cc gasoline engine and data collection at engine speeds of 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 and 5000 rpm; There is an increase in engine performance in the use of LPG gas fuel which tends to increase with increasing engine speed; The lowest fuel consumption was found with LPG gas fuel, with an average consumption difference of 0.06 kg/hour. There was an increasing trend in CO2 emissions with LPG gas fuel use with each increase in engine speed. There was an effect of LPG gas fuel use on the performance of a 110 cc gasoline engine.